An exploration of corporate criminal liability in international law for aiding and abetting international crimes in Africa - Ongeso, John Paul (My University, 2015)
At present, international law has not succeeded in establishing a way through which multinational corporations (MNCs) can be regulated effectively and compelled to adhere to international human rights standards. This poses a problem for states that rely heavily on the investment of MNCs for economic development. African states in particular compete for investment by reducing their regulatory mechanisms in order to attract MNCs. This allows MNCs to engage in practices that violate human rights and contribute to the commission of international crimes. This thesis seeks to address this problem by exploring how MNCs can be held criminally liable in international law if they are involved in serious human rights abuses and international crimes. In the twentieth century, two seminal events in international criminal justice illustrate that there was evidence that the notion of holding multinational corporations criminally liable was possible. These include i) the jurisprudence of the Allied Tribunals at Nuremberg after World War II which contemplated the possibility of corporate criminal liability and ii) the negotiations during the establishment of the International Criminal Court (ICC) in the 1990s which considered proposals for the extension of criminal liability to corporations. At the national level, many states provide for corporate criminal liability. This is often derived from the establishment of criminal liability of an official of the corporation. The United Kingdom and Australia, however, have successfully set out how a corporation may itself be found criminally liable without the need to derive its criminal liability from an official. These developments show that the idea of holding MNCs criminally liable, either through a derivative or non-derivative process, is possible and achievable. In particular, this thesis proposes that MNCs can be found criminally liable for aiding and abetting international crimes under Article 25(3)(c) of the Statute of the ICC. In proposing a way through which this can be achieved, this thesis does two things: i) it extracts principles of non-derivative criminal liability established in the United Kingdom and Australia and ii) it develops a theory of corporate criminal liability for aiding and abetting international crimes that incorporates these principles. This theory underpins the proposed new approach to the establishment of corporate criminal liability for aiding and abetting in the ICC.
Thesis (Ph.D.)--University of the Witwatersrand, Faculty of Commerce, Law and Management, School of Law, 2015.
Keywords: International crimes; Liability; Multinational corporations; Corporate criminal liability